(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
This paper discusses novelties proposed in a new Sales Law Directive Proposal. Firstly, explanation is given regarding the main reasons for the reform and how the higher level of consumer protection in sales contracts could be achieved. It has been noticed that the European legislator was focused on four important questions: the time frame for the burden of proof, notification on lack of conformity, the hierarchy of goods and the legal guarantee period. All these new solutions would be given through a new maximum harmonization directive which would appeal Directive 1999/44/EC on certain aspects of the sale of consumer goods and associated guarantees. Although the sales law reform is still in the legislative process phase, it was possible to discuss how the novelties would affect Croatian private law.